2001
DOI: 10.1016/s0014-5793(01)03100-3
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial peptides lactoferricin B and magainin 2 cross over the bacterial cytoplasmic membrane and reside in the cytoplasm

Abstract: The localization of immunolabelled antimicrobial peptides was studied using transmission electron microscopy. Staphylococcus aureus and Escherichia coli were exposed to lactoferricin B (17^41), lactoferricin B (17^31) and D-lactoferricin B (17^31). E. coli was also exposed to cecropin P1 and magainin 2. The lactoferricins were found in the cytoplasm of both bacteria. In S. aureus the amount of cytoplasmic lactoferricin B (17^41) was time-and concentration-dependent, reaching a maximum within 30 min. Cecropin P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 25 publications
4
80
0
1
Order By: Relevance
“…The mechanism by which Cecropin P1 disrupts the cell membrane of bacteria has been fully characterized. In contrast, Haukland et al (20) have proved that Lfcin B can penetrate the cell membrane without disruption; yet, Cecropin P1 has only been found to surround the membrane.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The mechanism by which Cecropin P1 disrupts the cell membrane of bacteria has been fully characterized. In contrast, Haukland et al (20) have proved that Lfcin B can penetrate the cell membrane without disruption; yet, Cecropin P1 has only been found to surround the membrane.…”
Section: Resultsmentioning
confidence: 93%
“…Some AMPs have been proven to penetrate the cell membrane and affect the intracellular targets within the cells (11)(12)(13); Lfcin B is one of these AMPs (14 -18). Some studies have indicated that Lfcin B leads to the depolarization of the cell membrane and does not lyse the cells (19); Lfcin B has been shown to inhibit the macromolecular synthesis of cells, which suggests that the intracellular targets of Lfcin B may exist (12,19,20).…”
mentioning
confidence: 99%
“…AMPs comprise part of the innate immune system of many organisms and help protect the host species from microbial invasion/infection. Current dogma dictates that the antimicrobial activity of these peptides is mediated through interaction of AMPs with target cell membranes and subsequent membrane disruption, although other mechanisms have been postulated [12][13][14]. The current study expands on previous work developing AMP-based detection assays for Escherichia coli and Salmonella typhimurium [15,16].…”
Section: Introductionmentioning
confidence: 77%
“…In general, AMPs are cationic, often amphipathic, which primarily kill bacteria by interacting and disrupting their cell membrane [10][11][12][13] . In a previous study, we introduced the 1-11 antimicrobial sequence of the human lactoferrin protein (hLf), the hLf1-11 peptide, as a potent AMP with capacity to reduce bacterial adhesion on titanium implants 8 .…”
Section: Introductionmentioning
confidence: 99%